Issues Of Development Of Motor Transport Logistics In Uzbekistan - Iminov Tukhtasin Nurmamatovich; Raximova Gulzoda Baxramovna (Genius Journals, 2021)
The article examines the best practices in the development of the transport and logistics sector, the issues of achieving diversification of foreign trade through the development of logistics forwarding services and multimodal logistics centers.
Keywords: Transport And Logistics Centers; Tariffs; Diversification; Freight Forwarding Services